Estado actual; Medios de promoción digitales en el sector hotelero del municipio de Paipa Boyacá. (2020)
This proposal seeks to identify the current state of the use of digital promotion media (social networks and specialized platforms) with a commercial focus for the hotel sector in the municipality of Paipa, department of Boyacá, with the objective of identifying the main aspects of this issue and its impact, in order to generate alternatives that allow strengthening the positioning of these establishments through digital tools in the market. According to (Suarez Salazar & Duarte Chaparro, 2017) the hotel sector of the municipality of Paipa is made up of 50 accommodation establishments of various categories, active in the database of the National Tourism Registry, the study reveals that the total establishments They have email and 21 of them are promoted through a virtual platform but it does not detail what type they are, nor the current status in qualitative and quantitative terms of the use of social networks in said sector, the above allows highlighting the importance in the application of the present proposal as it becomes a digital content management tool for administrators and owners of this important activity in the tourism sector. The following proposal has three phases mentioned below: Phase 1 to carry out an internal and external analysis diagnosis of the use of digital platforms and social networks; Phase 2 characterization of the accommodation establishments in the municipality of Paipa; Phase 3 creation of a training plan for the use of social networks in the hotel sector in the municipality of Paipa.